PENYUSUNAN ENSIKLOPEDIA PENDIDIKAN MELALUI INVENTARISASI LUMUT KERAK (LICHENES) DI DESA KUBU LIKU JAYA, KECAMATAN BATU KETULIS, KABUPATEN LAMPUNG BARAT - Siti Nurlaila; Triana Asih; Suharno Zen (Prodi Pendidikan Biologi FKIP Universitas Muhammadiyah Metro, 2022)
This study aimed to 1) determine the types of Lichens found in Kubu Liku Jaya Village, Batu Ketulis District, West Lampung Regency, 2) determine the feasibility of encyclopedias in the form of Biology learning resources on protist material of lichen sub material. . The approach and type of research used was descriptive qualitative with research methods and the research technique is purposive sampling. This research was conducted for 8 consecutive days. Based on the results of research at 4 observation stations, 18 species were found including Usnea filipendula, Parmelia sulcata, Physcia aipolia, Graphis scripta, Parmelia saxatilis, Physcia stellaris, Parmotrema perlatum, Graphis sp, Dirinaria picta, Cladonia portentosa, Centrelia centrarioides, Usnea coniotaps, Amandinea coniotaps , Scipta beauvoisii, Punctelia borreri, Xanthoparmelia conspersa, Parmeliopsis ambiguna, and Physcia tenella. The 6 families found were Usneaceae, Parmeliaceae, Physciaceae, Graphisceae, Cladoniaceae, and Lobariaceae. The orders found were 4 of them Lecanorales, Teloschitales, Ostropales, and Peltigerales. The results of the calculation of the species diversity index of lichens (Lichenes) in Kubu Liku Jaya Village, Batu Ketulis District, West Lampung Regency showed the number of 2.795 or moderate abundance, the highest was 0.229 for the Parmotrema perlatun species, while the lowest was 0.062 for the Scipta beauvoisii. The encyclopedia that had been developed from the research results had an average percentage score of 91.4% so it was feasible to be used as a source of learning biology in the form of an encyclopedia in high school class x Protista material.